2016
DOI: 10.1111/acer.13211
|View full text |Cite
|
Sign up to set email alerts
|

Current Heavy Alcohol Consumption is Associated with Greater Cognitive Impairment in Older Adults

Abstract: Background The acute consumption of excessive quantities of alcohol causes well-recognized neurophysiological and cognitive alterations. As people reach advanced age, they are more prone to cognitive decline. To date, the interaction of current heavy alcohol (ETOH) consumption and aging remain unclear. The current paper tested the hypothesis that negative consequences of current heavy alcohol consumption on neurocognitive function are worse with advanced age. Further, we evaluated the relations between lifetim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 47 publications
4
69
1
2
Order By: Relevance
“…Among male participants, dietary factors (eg, fried food, pickled food, spicy food and bacon intakes) were strongly associated with cognitive impairment. However, some other previously acknowledged risk factors such as alcohol drinking [39], smoking [40] were found to be non-significant in this study, which might be attributed to the fact that most of participants with cognitive impairment were women (71.9%). Furthermore, the percentage of cognitive impairment in our study was higher among the participants with hypertension, diabetes and CHD, which has been validated in previous researches [41][42][43].…”
Section: Viewpoints Research Theme 4: Health Transitions In Chinacontrasting
confidence: 85%
“…Among male participants, dietary factors (eg, fried food, pickled food, spicy food and bacon intakes) were strongly associated with cognitive impairment. However, some other previously acknowledged risk factors such as alcohol drinking [39], smoking [40] were found to be non-significant in this study, which might be attributed to the fact that most of participants with cognitive impairment were women (71.9%). Furthermore, the percentage of cognitive impairment in our study was higher among the participants with hypertension, diabetes and CHD, which has been validated in previous researches [41][42][43].…”
Section: Viewpoints Research Theme 4: Health Transitions In Chinacontrasting
confidence: 85%
“…Heavy alcohol consumption in older adults has been associated with faster decline in cognition in late middle age, particularly in men (Sabia et al, 2014). A history of alcohol dependence, even when it is not associated with current heavy alcohol use, can be associated with persistent cognitive impairment (Woods et al, 2016). Both alcohol dependence (Bates et al, 2005; Virag et al, 2015) and dependence on illicit substances including opioids, stimulants, and cannabis, are associated with executive dysfunction (Ersche et al, 2006; Lundqvist, 2005; Verdejo-Garcia and Perez-Garcia, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first study that has reported the harmful effect of alcohol consumption on fine motor limitation regardless of dose in European older men. 32,33 Motor skills are divided into two groups: gross motor skills, the larger movements of arms, legs, feet, or the entire body that are related to mobility and arm function, and fine motor skills. 34 The two groups are controlled by different brain regions.…”
Section: Discussionmentioning
confidence: 99%